Longitudinal evaluation of a countywide alternative to the Quality and Outcomes Framework in UK General Practice aimed at improving Person Centred Coordinated Care. Issue 7 (23rd July 2019) - Close, James; Fosh, Ben; Wheat, Hannah; Horrell, Jane; Lee, William; Byng, Richard; Bainbridge, Michael; Blackwell, Richard; Witts, Louise; Hall, Louise; Lloyd, Helen
Abstract : Objectives: To evaluate a county-wide deincentivisation of the Quality and Outcomes Framework (QOF) payment scheme for UK General Practice (GP). Setting: In 2014, National Health Service England signalled a move towards devolution of QOF to Clinical Commissioning Groups. Fifty-five GPs in Somerset established the Somerset Practice Quality Scheme (SPQS)—a deincentivisation of QOF—with the goal of redirecting resources towards Person Centred Coordinated Care (P3C), especially for those with long-term conditions (LTCs). We evaluated the impact on processes and outcomes of care from April 2016 to March 2017. Participants and design: The evaluation used data from 55 SPQS practices and 17 regional control practices for three survey instruments. We collected patient experiences ('P3C-EQ'; 2363 returns from patients with 1+LTC; 36% response rate), staff experiences ('P3C-practitioner'; 127 professionals) and organisational data ('P3C-OCT'; 36 of 55 practices at two time points, 65% response rate; 17 control practices). Hospital Episode Statistics emergency admission data were analysed for 2014–2017 for ambulatory-sensitive conditions across Somerset using interrupted time series. Results: Patient and practitioner experiences were similar in SPQS versus control practices. However, discretion from QOF incentives resulted in time savings in the majority of practices, and SPQS practice data showed a significant increase in P3C oriented organisational processes, with a moderate effect size (Wilcoxon signed rank test; p=0.01; r=0.42). Analysis of transformation plans and organisational data suggested stronger federation-level agreements and informal networks, increased multidisciplinary working, reallocation of resources for other healthcare professionals and changes to the structure and timings of GP appointments. No disbenefits were detected in admission data. Conclusion: The SPQS scheme leveraged time savings and reduced administrative burden via discretionary removal of QOF incentives, enabling practices to engage actively in a number of schemes aimed at improving care for people with LTCs. We found no differences in the experiences of patients or healthcare professionals between SPQS and control practices.